2006
DOI: 10.1007/s00425-006-0313-1
|View full text |Cite
|
Sign up to set email alerts
|

Varied growth, biomass and cellulose content in tobacco expressing yeast-derived invertases

Abstract: The effects of the expression of yeast-derived apoplastic (AI) and cytosolic (CI) invertases (EC 3.2.1.26) on biomass and structural carbohydrate accumulation in tobacco (Nicotiana tabacum L. cv. Xanthi) were evaluated. Transgenic tobacco plants expressing AI or CI under the control of either a tandem repeat of the Cauliflower Mosaic Virus 35S promoter (2X35S), or a promoter that drives xylem-localized expression (Petroselinum crispum 4-coumarate:CoA ligase promoter; 4CL) were generated. Yeast-derived invertas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…The authors observed a similar phenotype when the extracellular-located yeast invertase was driven under a meristem-specific promoter, which was observed in several other studies (e.g. Lerchl et al, 1995;Fukushima et al, 2001;Canam et al, 2006), confirming the principal function of a yeast-derived invertase in plants.…”
Section: Discussionsupporting
confidence: 79%
“…The authors observed a similar phenotype when the extracellular-located yeast invertase was driven under a meristem-specific promoter, which was observed in several other studies (e.g. Lerchl et al, 1995;Fukushima et al, 2001;Canam et al, 2006), confirming the principal function of a yeast-derived invertase in plants.…”
Section: Discussionsupporting
confidence: 79%
“…The authors observed a similar phenotype when the extracellular-located yeast invertase was driven under a meristem-specific promoter, which was observed in several other studies (e.g. Lerchl et al, 1995;Fukushima et al, 2001;Canam et al, 2006), confirming the principal function of a yeast-derived invertase in plants.…”
Section: Discussionsupporting
confidence: 79%
“…Overexpression of these two genes together significantly increases plant height, with postulated increase in cellulose content and overall plant biomass. Similarly, heterologous expression of invertase in tobacco plants resulted in significant increase in biomass and in cellulose content [90]. Moreover, SPS overexpression led to enhanced plant growth and fiber elongation in tobacco models which can be explained by elevated concentrations of sink sucrose pools compared to wild-type plants [91].…”
Section: Genetic Manipulation Of the Cellulose Synthesis Pathwaymentioning
confidence: 99%